Prevalence of asymptomatic pharyngel carriage of B-hemolytic Group A Streptococcus pyogens among school going children of age 5-12 years in Bharatpur, Nepal - Raza, S; Kundu, KK; Dutta, SK (Journal of Kathmandu Medical College, 2014)
Background: β- haemolytic Group A Streptococcus pyogens infection is a common cause of bacterial pharyngitis among children. Children are the target population for pharyngitis as well as other suppurative and non-suppurative infections. Objectives: The objectives of this study are to find out the rate of asymptomatic throat carriage of Streptococcus pyogens and to study antibiotic susceptibility pattern of the isolates. Methods: Total 106 randomly selected children between five to 12 years were included in this study. Throat swabs collected were inoculated on 5% sheep blood agar and incubated for 24-48 hours at 37°C. Identifi cation of Group A Streptococcus pyogens was done by β-haemolytic colony, Bacitracin sensitivity, Co-trimoxazole resistivity and catalase negativity. Antibiotic susceptibility test was performed on Muller-Hinton agar containing 5% sheep blood by modifi ed Kirby-Bauer disc diffusion method. Results were interpreted as per National Committee for the Clinical Standards Guidelines. Results: Of total 106 throat swabs Group A Streptococcus pyogens was isolated in 15 (14.15%) cases. Among the isolates seven (46.7%) were from male children whereas eight (53.3%) were from female children. Out of the 15 isolates 100% were sensitive to penicillin and its derivatives whereas 13.2%, 6.7% and 6.7% of the isolates were resistant to Erythromycin, Chloramphenicol and Ciprofl oxacin respectively. Similarly Azithromycin was found to be 100% sensitive. Conclusion: Regular screening is needed to keep the GAS infection and carrier state in check as well as to prevent from further development of complications. DOI: http://dx.doi.org/10.3126/jkmc.v2i1.10537 Journal of Kathmandu Medical College, Vol. 2, No. 1, Issue 3, Jan.-Mar., 2013: 18-20